Perlindungan Hukum Terhadap Masyarakat Akibat Pemberitaan Pers - Samsul Wahidin (Fakultas Hukum Universitas Islam Indonesia, 2000)
The reformation of the mass media, especially printed press, in Indonesia has already caused a new paradigm of freedom of press. In one hand, the press freedom is a reflection of the freedom of expressing ideas and of obtaining information, which is assuredby the constitution. This press freedom, however, is always put forward by journalists as one of the element of democratic principles. On the other hand, the freedom face problems of urgently required legal protection to societies as the consequence of the invalid pressrelease. As a result, the press arrogance emerges. The legal protection toward the press release victims requires taking a tes inpractice as a balance of the press freedom.